Evaluation of Bone Quality in Patients with Bruxism - Kotanli, Sedef; Ozturk, Elif Meltem Aslan; Dogan, Mehmet Emin; Uluısık, Nurbanu (Current Medical Imaging, 2024)
Background Bruxism may cause increased alveolar bone thickness and density and irregular enlargement of the periodontal space. Aim This study aimed to evaluate the mandibular bone quality using radio-morphometric indices and Fractal Dimension (FD) analysis in orthopantomography (OPG). Material and Methods OPGs of 100 patients, 50 bruxers and 50 non-bruxers, were included in this study. Values, such as mental index (MI), panoramic mandibular index (PMI), gonial index (GI), antegonial notch depth (AND), mandibular cortical index (MCI), and antegonial index (AI), were calculated in OPG. Eight bilateral areas of interest (ROI) were selected on ort for FD analysis: ROI 1, mandibular condyle; ROI 2, mandibular ramus; ROI 3, mandibular angulus; and ROI 4, mandibular mental area. Results MI, PMI, and AND values were higher in bruxers than in the control group (p<0.05). MCI and AI values calculated on both sides were not statistically significantly related in bruxism and control group individuals (p>0.05). As a result of the calculations, the FD values of the left condyle (p=0.02) and left angulus (p=0.03) areas showed a statistically significant difference between individuals with and without bruxer. No statistically significant difference was found in the FD measurements calculated from the ramus and mental areas on the right and left sides (p>0.05). The relationship between FD values and gender in these areas was examined, and no statistically significant difference was found (p<0.05). Conclusion In dentistry, bruxism can be diagnosed and treated by measuring MI, PMI, and AND values. No difference was found in mandibular cortical bone thickness in bruxers and non-bruxers, according to AI and MCI. The mean GI measured on the right side differed between groups. FD values of the mandibular trabecular bone were affected by bruxism in the right condyle and right angulus areas.
Keywords: Radio-morphometric indices